First observations of minority ion (H+) structuring in stimulated radiation during second electron gyroharmonic heating experiments. Issue 8 (29th April 2013) - Bordikar, M. R.; Scales, W. A.; Samimi, A. R.; Bernhardt, P. A.; Brizcinski, S.; McCarrick, M. J.
Abstract : [1] This work presents the first observations of unique narrowband emissions ordered near the hydrogen ion (H + ) gyrofrequency ( f c H ) in the stimulated electromagnetic emission spectrum when the transmitter is tuned near the second electron gyroharmonic frequency (2 f c e ) during ionospheric modification experiments. The frequency structuring of these newly discovered emission lines is quite unexpected since H + is known to be a minor constituent in the interaction region which is near 160 km altitude. The spectral lines are typically shifted from the pump wave frequency by harmonics of a frequency about 10% less than f c H (≈ 800 Hz) and have a bandwidth of less than 50 Hz which is near the O + gyrofrequency f c O . A theory is proposed to explain these emissions in terms of a parametric decay instability in a multi‐ion species plasma due to possible proton precipitation associated with the disturbed conditions during the heating experiment. The observations can be explained by including several percent H + ions into the background plasma. The implications are new possibilities for characterizing proton precipitation events during ionospheric heating experiments. Key Points: First observations of H+ ion structuring in SEE during heating experiment Disturbed magnetic conditions imply proton precipitation likely plays a key role Theory is provided to explain emissions by PDI in multi‐ion plasma